1992
DOI: 10.1001/jama.1992.03480080060027
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Lymphomas and Other Cancers in HIV-Infected and HIV-Uninfected Patients With Hemophilia

Abstract: HIV infection has restricted effects on cancer incidence that are only partly explained by immunosuppression. Paradoxically, improvements in therapy of HIV infection that prolong survival may lead to further increases in HIV-associated lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(28 citation statements)
references
References 24 publications
4
24
0
Order By: Relevance
“…The recognition of this association has prompted the speculation that CKS frequently develops in immunosuppressed persons; the association of the 2 diseases was also suggested to be dependent on a common clinical pattern instead of a common cell of origin, and the 2 possibilities are not mutually exclusive. Chronic leukemia, mainly of lymphocytic type (CLL), was, as expected, the most frequent type in our series: 55% compared with an overall proportion of 33.2% in all Jews of the same age range during the period -1992(Israel Cancer Registry, 1993. Furthermore, patients with a CLL, a B-cell disease where both primary and secondary antibody response are depressed, show a lower mean age at diagnosis than those with other primary neoplasms, related to subsequent CKS.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The recognition of this association has prompted the speculation that CKS frequently develops in immunosuppressed persons; the association of the 2 diseases was also suggested to be dependent on a common clinical pattern instead of a common cell of origin, and the 2 possibilities are not mutually exclusive. Chronic leukemia, mainly of lymphocytic type (CLL), was, as expected, the most frequent type in our series: 55% compared with an overall proportion of 33.2% in all Jews of the same age range during the period -1992(Israel Cancer Registry, 1993. Furthermore, patients with a CLL, a B-cell disease where both primary and secondary antibody response are depressed, show a lower mean age at diagnosis than those with other primary neoplasms, related to subsequent CKS.…”
Section: Discussionsupporting
confidence: 80%
“…It is not clear whether lymphomas and KS share an alteration of the phenotype of the infected B-cell; however, KS have been found to be less frequently in individuals who contract HIV through blood transfusion (Beral et al, 1990); however, it was founded by others (Serraino et al, 1992). While it is rare in hemophiliacs population (Rabkin et al, 1992), it have been suggested that HHV-8 (or another 'KS agent') is cellassociated. Here we report a population-based study of secondary CKS in Israel and its association with the type of primary neoplasm and the origin of the patients.…”
mentioning
confidence: 99%
“…As the risk of NHL in AIDS and other immunodeficiency states is related to the degree of immune dysregulation (31), it could be that the apparently low risk of HIV-associated lymphoma in Nigeria, as in some other African countries, is the result of competing mortality, particularly from infectious diseases in AIDS patients with relatively low levels of immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the HIV genome is usually absent in HIV-associated NHL tissue (7,8). The rate of NHL does not generally vary with the risk factor for acquiring HIV infection, but the incidence of both KS and NHL is lower in hemophiliacs infected with HIV than in HIV-positive homosexuals (14,19). Interestingly, an increased risk of developing NHL has been found in patients with KS, herpes simplex virus co-infection and a low neutrophil count (20).…”
Section: Discussionmentioning
confidence: 99%